Fuzzy subtractive clustering technique applied to demand response in a smart grid scope - Melício, Rui (2014)
This paper focuses on demand response in a smart grid scope using a fuzzy subtractive clustering technique for a favorable modeling of demand response. Domestic consumption is classified into profiles in order to cover the adequate modeling. The fuzzy subtractive clustering technique is applied to on a case study of domestic consumption demand response with three scenarios and a comparison of the results is presented. The demand response developed model intends to support consumer´s decisions given a compromise between the consumption imperative needs and possible economical benefits due to reshape and reschedule.